Numerical study of oscillation characteristics in T-shaped cryogenic helium tube. (April 2023) - Niu, Yafeng; Hu, Lulu; Chen, Pengfan; Liu, Yingwen; Gao, Bo
Abstract: Thermoacoustic oscillations generally exist in combustion devices and cryogenic systems, causing system instability and other problems. The actual cryogenic system has complex pipe connections, however, there are few studies on the thermoacoustic oscillation of complex structures, which brings challenges to suppressing thermoacoustic instability. Therefore, this study focuses on the T-shaped helium tube existing in the actual cryogenic system and explores the oscillation characteristics of the complex cryogenic thermoacoustic system. With the change of branch position and length, mode transition phenomenon appears. We obtained the effects of the branch position and length on the amplitude and frequency of each mode and found that the self-excited oscillation in the T-shaped tube could be suppressed to some extent by choosing the proper length and position of the branch tube. Further research found that the first mode of the oscillating pressure in the main and branch tube was in-phase synchronized, and the second mode was antiphase synchronized. By linking the flow direction with the oscillation mode, it is found that the first mode corresponds to the first flow direction, and the second mode corresponds to the second or third flow direction. The finding is valuable for understanding thermoacoustic oscillations in T-tubes and provides a reference for controlling the self-excited oscillation of complex cryogenic systems. Highlights: The effects of two critical parameters on thermoacoustic oscillations of T-shaped cryogenic helium tubes are studied. The mode transition phenomenon is found, and the mode variation law is obtained. Choosing the proper branch position and length can suppress self-excited oscillation. The asynchrony of oscillation pressure in the main and branch tube is reflected in the second mode. The corresponding relationship between the oscillation mode and the flow direction is revealed.